Vague Soft Hypergroups and Vague Soft Hypergroup Homomorphism. (31st March 2014) - Selvachandran, Ganeshsree; Salleh, Abdul Razak
Abstract : We introduce and develop the initial theory of vague soft hyperalgebra by introducing the novel concept of vague soft hypergroups, vague soft subhypergroups, and vague soft hypergroup homomorphism. The properties and structural characteristics of these concepts are also studied and discussed.